Possibility Of Using Cardboard Mill Sludge In Remediation Of Contaminated Sediment - Prica, Miljana; Dalmacija, Milena; Dalmacija, Božo; Tricković, Jelena; Milošević, Rastko (Journal of Graphic Engineering and Design, 2023)
The sludge from cardboard mill is commonly landfilled, but it could be recycled into production on-site or reused in some other way. In this study the use of sludge from cardboard mill as stabilizing agent in the solidification/stabilization (S/S) treatment of lead polluted sediment was examined. The effectiveness of S/S treatment was evaluated by determining cumulative percentage of lead leached and by applying different leaching tests. Applied S/S treatment was effective in immobilizing lead irrespective of high concentration in the untreated sample.